(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
In order to investigate the effect of a yeast on laying hens performance and live weight, one hundred Rodonit-3 breed laying hens (75 week of age), were selected and randomly allocated to 25 pens containing 4 laying hens each with 6 replicates and assigned to receive one of 4 dietary treatments (1. Control, 2. Yeast 2%, 3.Yeast 4%, 4.Yeast 6%). The results showed that egg production and egg weight not significantly different, live weight and feed intake significant differences. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 114-116